Retirement planning behaviour among staff in Pejabat Daerah & Tanah Marang, Terengganu / Siti Munirah Mohd Azam - Mohd Azam, Siti Munirah (2014)
The research study titled "Retirement Planning Behaviour among Staff in Pejabat Daerah & Tanah Marang, Terengganu”. The objectives of this research study to identify the level of awareness about retirement planning behaviour, to identify the relationship between each independent variable (financial literacy, awareness on savings and educational level) with the retirement planning behavior among staff in Pejabat Daerah & Tanah Marang, Terengganu and to identify between working experience of the staff regarding to retirement planning behavior. The researchers use data collection method of convenience sampling under purposive sampling. As a result, all objectives from the research study are supported.